Preparation method and application of copper-tin composite electrode material based on waste cupronickel

Through the composite electrodeposition-low-temperature calcination process, copper-tin composite electrode materials were prepared, which solved the problems of the complex preparation of existing electrochemical glucose sensors and the complex recycling process of waste copper, and achieved efficient and low-cost glucose detection and effective utilization of waste copper resources.

CN119685616AActive Publication Date: 2025-03-25NORTHEASTERN UNIV CHINA
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411837695.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-25
Estimated Expiration
2044-12-13

AI Technical Summary

Technical Problem

The existing electrochemical glucose sensors are limited in their application in diabetes management due to their complex preparation methods, expensive and susceptible to environmental factors. At the same time, the recycling process of waste copper alloy is complex and costly, making it difficult to effectively utilize this important copper metal resource.

Method used

Through a simple composite electrodeposition-low-temperature calcination process, a copper-coated tin oxide composite material is prepared by using the sulfuric acid dissolving solution of waste copper and tin oxide powder, and a copper-tin composite electrode material rich in vacancy and defects is obtained.

Benefits of technology

This method not only realizes efficient glucose detection, has excellent stability and selectivity, but also effectively utilizes waste copper resources, reduces production costs, simplifies the process flow, and is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119685616A_ABST
    Figure CN119685616A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a copper-tin composite electrode material based on waste cupronickel, and belongs to the field of preparation of copper-based composite materials recovered from waste cupronickel and electrochemical detection of glucose. A waste cupronickel sulfuric acid solution is used as a copper metal precursor, a silver wire is used as a cathode, and a waste cupronickel sulfuric acid solution added with tin oxide powder is used as an electrolyte; the preparation method comprises the following steps: synthesizing a copper-coated tin oxide composite material on a silver wire by taking a tin oxide as a cathode and a waste white copper sheet as an anode through an electrochemical composite electrodeposition process, and carrying out low-temperature calcination on the copper-coated tin oxide composite material in argon-hydrogen mixed gas to obtain the copper-tin composite electrode material. The copper-tin composite electrode material prepared through the method has good electrochemical performance, the preparation process is simple, and application of the copper-tin composite material in the field of electrochemical glucose sensors can be promoted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of preparation of copper-based composite materials recovered from waste white copper and electrochemical detection of glucose, and specifically relates to a preparation method of a copper-tin composite electrode material based on waste white copper and application of the same in glucose detection. Background Art

[0002] Diabetes is one of the deadly diseases that causes a large number of deaths worldwide every year. It also leads to several other complications such as kidney failure, stroke and blindness. The number of diabetic patients has also been increasing in recent years. The main cause is insufficient insulin secretion in the pancreas, which leads to elevated blood sugar, but it is also affected by factors such as genetics, lifestyle and viruses. Maintaining normal blood sugar levels is a key strategy to prevent diabetes-related complications, so it is particularly important to develop low-cost, simple and rapid glucose detection methods. Electrochemical glucose sensors have attracted much attention due to their high sensitivity, low detection limit, rapid response, simple operation and other advantages. However, traditional electrochemical enzyme sensors are subject to many limitations in practical applications due to their complex preparation methods, high prices, and easy inactivation due to environmental factors such as temperature and pH. Transition metal-based non-enzymatic glucose sensors have attracted widespread attention from researchers due to their low cost, good stability and excellent catalytic activity.

[0003] The study found that copper not only exhibits excellent conductivity in the process of glucose electrocatalytic oxidation and detection, but also serves as a good active site center. On the other hand, cupronickel is a nickel-copper alloy with copper as the base metal and nickel as the main alloying element, with a silvery-white metallic luster. Because copper and nickel have similar atomic radii, they can be infinitely soluble in each other, and their corrosion resistance, heat resistance and cold resistance are also excellent. In order to improve the structure and properties of the alloy, zinc, iron or manganese are often added to obtain zinc cupronickel, iron cupronickel and manganese cupronickel alloys with more extensive uses. In recent years, with the rapid economic growth and industrialization process, the demand and consumption of cupronickel alloys have continued to increase, resulting in a large amount of waste cupronickel alloys. Due to the depletion of natural copper-nickel ore resources and the requirements of environmental protection, cupronickel alloy waste has gradually become an important copper metal resource. For large pieces of waste cupronickel alloy waste, because it is difficult to crush and difficult to achieve metal separation by pyrometallurgy, most of them are recycled by traditional hydrometallurgical processes such as leaching, extraction and electrowinning. Although the electrodeposition process has the advantages of high dissolution efficiency, good working conditions, and high degree of resource utilization, it still needs to solve the problems of complex process flow, large amount of reagents, and secondary environmental pollution in industrial applications. Therefore, it is particularly important to seek a simple regeneration process for waste white copper.

[0004] Compared with single metal materials, bimetallic materials often show better electron transfer rate and more excellent electrocatalytic activity due to the synergistic effect between the two elements. Based on this, the present invention selects copper and tin as two elements and constructs copper-tin-based bimetallic catalysts for non-enzymatic electrochemical glucose detection through different methods. Summary of the invention

[0005] The main purpose of the present invention is to provide a simple method for preparing a copper-tin composite electrode material with excellent glucose detection performance using waste white copper as a copper metal precursor. Specifically, a waste white copper sulfuric acid solution is used as a copper metal precursor, a silver wire is used as a cathode, and a waste white copper sulfuric acid solution with tin oxide powder added is used as an electrolyte. A copper-coated tin oxide composite material is quickly synthesized on the silver wire through a simple electrochemical composite electrodeposition process. The copper-coated tin oxide composite material is calcined at a low temperature in an argon-hydrogen mixed gas to obtain a copper-tin composite electrode material rich in vacancies and defects.

[0006] The present invention provides a method for preparing a copper-tin composite electrode material based on waste white copper, comprising the following steps:

[0007] 1) calcining the waste white copper to obtain surface oxidized waste white copper sheets;

[0008] 2) soaking the waste copper-nickel sheet obtained in step 1) in a sulfuric acid solution and heating and dissolving the waste copper-nickel sheet to obtain a sulfuric acid solution of the waste copper-nickel sheet;

[0009] 3) using the sulfuric acid solution of the waste white copper obtained in step 2) as a copper metal precursor, and adding tin dioxide powder as an electrolyte to dissolve the remaining waste white copper sheets or the waste white copper sheets after calcination as an anode, and using a silver wire as a cathode to perform an electrolytic reaction, and cleaning and drying the cathode after electrolysis to obtain a composite material of copper-coated tin oxide, i.e., a precursor of a copper-tin composite electrode material;

[0010] 4) calcining the precursor material obtained in step 3) in an argon-hydrogen mixed atmosphere in a tubular furnace to obtain a copper-tin composite electrode material based on waste white copper.

[0011] The scrap white copper of the present invention is B17 type scrap nickel white copper, which mainly contains three metal elements of copper, zinc and nickel, wherein the copper content is 82%, the zinc content is 15% and the nickel content is 3%.

[0012] The calcination process in step 1) of the present invention is carried out in a muffle furnace, the calcination temperature is 500° C. to 800° C., and the calcination time is 60 min to 180 min.

[0013] The concentration of the sulfuric acid solution of the present invention is 0.01 mol / L to 5 mol / L.

[0014] The soaking temperature in step 2) of the present invention is 25° C. to 95° C., and the reaction time is 50 min to 130 min.

[0015] The concentration of the sulfuric acid solution of the waste white copper in the present invention is 0.005 mol / L to 3 mol / L.

[0016] The added amount of the tin dioxide powder of the present invention is 4 mg / L to 15 mg / L.

[0017] The electrolysis method of the present invention has a voltage of -3 to -1.1 V and a cathode current density of 0.01 A / cm 2 ~0.111A / cm 2 The electrolysis temperature is 25°C ~ 55°C, the electrolysis time is 20min ~ 60min, and the stirring speed is 200r / min ~ 500r / min.

[0018] The chemical reaction of the electrolysis process of the present invention is as follows:

[0019] Anode reaction: M→xe+M xe ; Cathode reaction: Cu 2+ +2e→Cu.

[0020] The precursor of the copper-tin composite electrode material of the present invention is Cu@SnO2, and during the copper deposition process, tin dioxide nanoparticles are coated and deposited on the electrode surface.

[0021] The invention discloses calcining in an argon-hydrogen mixed atmosphere, wherein the molar fraction of hydrogen in the mixed gas is 2-10%, the calcining temperature is 300-600°C, and the calcining time is 1-3 hours.

[0022] A second aspect of the present invention provides a copper-tin composite electrode material based on waste white copper, which is prepared according to the method described in the first aspect.

[0023] A third aspect of the present invention provides an application of a copper-tin composite electrode material based on waste white copper in a glucose sensor.

[0024] The copper-tin composite electrode material exhibits excellent stability, selectivity and good analytical detection performance.

[0025] The excellent analytical detection performance comes from the rich interface structure and the synergistic catalytic effect of bimetallic copper and tin.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] 1. The present invention adopts a simple composite electrodeposition-low temperature calcination process, and uses the waste copper-nickel acid solution with tin dioxide powder added as the electrodeposition solution to prepare a copper-tin composite electrode material with excellent detection performance. The implementation of this method not only helps to broaden the research ideas on the resource utilization of waste copper-nickel, but also can obtain a new type of glucose sensor material, and reduce the cost, which has a high economic value.

[0028] 2. The present invention obtains transition metal-based composite electrode materials through a simple composite electrodeposition-low temperature calcination process, achieving the purpose of efficient glucose detection. It not only realizes the one-step production from secondary resources to glucose sensors, but also effectively avoids the problem of multi-metal separation and high separation cost in the treatment process of waste white copper.

[0029] 3. Compared with the existing sensor preparation process, this method has a short preparation process from secondary resources to composite electrode materials, a simple process, low process cost, low equipment requirements, and is easy to achieve large-scale production.

[0030] 4. The copper-tin composite electrode material prepared by the method of the present invention has good stability, selectivity and good analytical detection performance. The present invention opens up a new way for efficient and low-cost non-enzymatic glucose detection, and at the same time provides a new research idea for the comprehensive and efficient recovery and utilization of waste white copper. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 Morphological results of copper-tin composite electrode materials;

[0032] Figure 2 Distribution of copper element on the surface of copper-tin composite electrode material;

[0033] Figure 3 Distribution of tin element on the surface of copper-tin composite electrode material;

[0034] Figure 4 Distribution of oxygen elements on the surface of copper-tin composite electrode materials;

[0035] Figure 5 Electrochemical impedance spectroscopy of copper-tin composite electrode material;

[0036] Figure 6 Multiple square wave cycle curves of copper-tin composite electrode material. DETAILED DESCRIPTION

[0037] The embodiment of the present invention discloses a method for preparing a copper-tin composite electrode material based on waste white copper. The waste white copper used is B17 type waste nickel white copper, which mainly contains three metal elements of copper, zinc and nickel, wherein the copper content is 82%, the zinc content is 15% and the nickel content is 3%. The obtained copper-tin composite electrode material is applied to a non-enzymatic glucose electrochemical sensor.

[0038] A method for preparing a copper-tin composite electrode material based on waste white copper, the specific steps are as follows:

[0039] 1) calcining the waste white copper to obtain surface oxidized waste white copper sheets; wherein the calcination process is carried out in a muffle furnace, the calcination temperature is 500° C. to 800° C., and the calcination time is 60 min to 180 min;

[0040] 2) soaking the waste white copper sheet obtained in step 1) in a sulfuric acid solution with a concentration of 0.01 mol / L to 5 mol / L for heating and dissolving, the soaking temperature is 25° C. to 95° C., and the reaction time is 50 min to 130 min to obtain a sulfuric acid solution of the waste white copper;

[0041] 3) The sulfuric acid solution (0.005 mol / L to 3 mol / L) of the waste white copper in step 2) is taken as a copper metal precursor, and after adding tin dioxide powder, it is used as an electrolyte, and the amount of tin dioxide powder added is 4 mg / L to 15 mg / L. The remaining waste white copper sheet or the waste white copper sheet after oxidation treatment is used as an anode, and the silver wire is used as a cathode to perform an electrolytic reaction. The voltage of the electrolysis process is -3V to -1.1V, and the cathode current density is 0.01A / cm 2 ~0.111A / cm 2 The electrolysis temperature is 25°C to 55°C, the electrolysis time is 20min to 60min, the stirring speed is 200r / min to 500r / min, and the cathode after electrolysis is cleaned and dried to obtain a composite material of copper-coated tin oxide, i.e., a precursor of a copper-tin composite electrode material;

[0042] 4) Calcine the precursor material obtained in step 3) in a tube furnace in an argon-hydrogen mixed atmosphere to obtain a copper-tin composite electrode material based on waste copper white, wherein the molar fraction of hydrogen in the mixed gas is 2% to 10%, the calcination temperature is 300° C. to 600° C., and the calcination time is 1 to 3 hours.

[0043] Example 1

[0044] The waste white copper sheet after surface oxidation treatment was used as the anode, 200 mL of sulfuric acid solution of waste white copper with a concentration of 0.5 mol / L and 12 mg of tin dioxide powder added was taken as the electrolyte, and the silver wire with a clean surface was used as the cathode. Then, the electrolysis was stirred in a water bath at a speed of 200 r / min for 20 minutes, and the electrolysis temperature was 30°C. The electrode material was obtained by constant current electrolytic deposition, and the deposition current was 0.01 A / cm 2After cleaning and drying the cathode after electrolysis, a precursor of a copper-tin composite electrode material is obtained, and the precursor material is calcined in an argon-hydrogen mixed atmosphere in a tubular furnace, wherein the molar fraction of hydrogen in the mixed gas is 8%, the calcination temperature is 300°C, and the calcination time is 1 hour, to obtain a copper-tin composite electrode material based on waste white copper.

[0045] The morphology of the copper-tin composite electrode material prepared in Example 1 is as follows: Figure 1 As shown, the distribution of copper, tin and oxygen elements on the surface are as follows Figure 2 , 3 and 4. The electrochemical impedance spectrum of the copper-tin composite electrode material is shown in Figure 5 As shown, the multiple square wave cycle curves are as follows Figure 6 shown.

[0046] Example 2

[0047] The remaining waste white copper sheet dissolved in the sulfuric acid solution was used as the anode, 200 mL of sulfuric acid solution of waste white copper with a concentration of 0.1 mol / L and 8 mg of tin dioxide powder added was taken as the electrolyte, and the silver wire with a clean surface was used as the cathode, and then electrolyzed for 35 minutes at a speed of 300 r / min in a water bath, and the electrolysis temperature was 55°C. The electrode material was obtained by constant voltage electrolytic deposition, and the deposition voltage was -2V. After cleaning and drying the cathode after electrolysis, the precursor of the copper-tin composite electrode material was obtained, and the precursor material was calcined in an argon-hydrogen mixed atmosphere in a tubular furnace, wherein the molar fraction of hydrogen in the mixed gas was 6%, the calcination temperature was 300°C, and the calcination time was 2 hours, to obtain a copper-tin composite electrode material based on waste white copper.

[0048] Example 3

[0049] The waste white copper sheet after surface oxidation treatment was used as the anode, 200 mL of sulfuric acid solution of waste white copper with a concentration of 1 mol / L and 10 mg of tin dioxide powder added was taken as the electrolyte, and the silver wire with a clean surface was used as the cathode. Then, the electrolysis was stirred in a water bath at a speed of 500 r / min for 60 minutes, and the electrolysis temperature was 35°C. The electrode material was obtained by constant current electrolytic deposition, and the deposition current was 0.05 A / cm 2 After cleaning and drying the cathode after electrolysis, a precursor of a copper-tin composite electrode material is obtained, and the precursor material is calcined in an argon-hydrogen mixed atmosphere in a tubular furnace, wherein the molar fraction of hydrogen in the mixed gas is 2%, the calcination temperature is 500°C, and the calcination time is 2 hours, to obtain a copper-tin composite electrode material based on waste white copper.

[0050] Example 4

[0051] The remaining waste white copper sheet dissolved in the sulfuric acid solution was used as the anode, 200 mL of sulfuric acid solution of waste white copper with a concentration of 3 mol / L and 16 mg of tin dioxide powder added was taken as the electrolyte, and the silver wire with a clean surface was used as the cathode, and then electrolyzed for 60 minutes at a speed of 500 r / min in a water bath, and the electrolysis temperature was 40°C. The electrode material was obtained by constant voltage electrolytic deposition, and the deposition voltage was -1V. After cleaning and drying the cathode after electrolysis, the precursor of the copper-tin composite electrode material was obtained, and the precursor material was calcined in an argon-hydrogen mixed atmosphere in a tubular furnace, wherein the molar fraction of hydrogen in the mixed gas was 2%, the calcination temperature was 600°C, and the calcination time was 1 hour, to obtain a copper-tin composite electrode material based on waste white copper.

[0052] The present invention has been described through the above embodiments, but it should be understood that the above embodiments are only for the purpose of example and description, and are not intended to limit the present invention to the scope of the described embodiments. In addition, it can be understood by those skilled in the art that the present invention is not limited to the above embodiments, and more variations and modifications can be made according to the teachings of the present invention, and these variations and modifications all fall within the scope of the protection claimed by the present invention.

Claims

1. A method for preparing a copper-tin composite electrode material based on waste white copper, characterized in that: Using waste cupronickel sulfuric acid solution as copper metal precursor, silver wire as cathode, waste cupronickel sulfuric acid solution with tin oxide powder added as electrolyte, and waste cupronickel sheet as anode, a copper-coated tin oxide composite material is synthesized on the silver wire through an electrochemical composite electrodeposition process, and the copper-coated tin oxide composite material is calcined at low temperature in an argon-hydrogen mixed gas to obtain a copper-tin composite electrode material.

2. The method for preparing a copper-tin composite electrode material based on waste white copper according to claim 1, characterized in that: The following steps are involved: 1) calcining the waste white copper to obtain surface oxidized waste white copper sheets; 2) soaking the waste copper-nickel sheet obtained in step 1) in a sulfuric acid solution and heating and dissolving the waste copper-nickel sheet to obtain a sulfuric acid solution of the waste copper-nickel sheet; 3) using the sulfuric acid solution of the waste white copper obtained in step 2) as a copper metal precursor, and adding tin dioxide powder as an electrolyte to dissolve the remaining waste white copper sheets or the waste white copper sheets after calcination as an anode, and using a silver wire as a cathode to perform an electrolytic reaction, and cleaning and drying the cathode after electrolysis to obtain a composite material of copper-coated tin oxide, i.e., a precursor of a copper-tin composite electrode material; 4) calcining the precursor material obtained in step 3) in an argon-hydrogen mixed atmosphere in a tubular furnace to obtain a copper-tin composite electrode material based on waste white copper.

3. The method for preparing a copper-tin composite electrode material based on waste white copper according to claim 2, characterized in that: The scrap white copper is B17 type scrap nickel white copper, which mainly contains three metal elements: copper, zinc and nickel, wherein the copper content is 82%, the zinc content is 15% and the nickel content is 3%.

4. The method for preparing a copper-tin composite electrode material based on waste white copper according to claim 2, characterized in that: Step 1) The calcination process is carried out in a muffle furnace, the calcination temperature is 500° C. to 800° C., and the calcination time is 60 min to 180 min.

5. The method for preparing a copper-tin composite electrode material based on waste white copper according to claim 2, characterized in that: The concentration of the sulfuric acid solution in step 2) is 0.01 mol / L to 5 mol / L; the soaking temperature is 25° C. to 95° C., and the reaction time is 50 min to 130 min.

6. The method for preparing a copper-tin composite electrode material based on waste white copper according to claim 2, characterized in that: Step 3) The concentration of the sulfuric acid solution of the waste white copper is 0.005 mol / L to 3 mol / L; the amount of tin dioxide powder added is 4 mg / L to 15 mg / L.

7. The method for preparing a copper-tin composite electrode material based on waste white copper according to claim 2, characterized in that: In step 3), the voltage of the electrolysis process is -3V to -1.1V, and the cathode current density is 0.01A / cm 2 ~0.111A / cm 2 The electrolysis temperature is 25°C ~ 55°C, the electrolysis time is 20min ~ 60min, and the stirring speed is 200r / min ~ 500r / min.

8. The method for preparing a copper-tin composite electrode material based on waste white copper according to claim 2, characterized in that: The precursor of the copper-tin composite electrode material is Cu@SnO2, and during the copper deposition process, tin dioxide nanoparticles are coated and deposited on the electrode surface.

9. The method for preparing a copper-tin composite electrode material based on waste white copper according to claim 2, characterized in that: Step 4) calcining in an argon-hydrogen mixed atmosphere, wherein the molar fraction of hydrogen in the mixed gas is 2% to 10%, the calcination temperature is 300° C. to 600° C., and the calcination time is 1 h to 3 h.

10. Use of the copper-tin composite electrode material based on waste white copper obtained by the preparation method according to any one of claims 1 to 9 in a glucose sensor.

Citation Information

Patent Citations

  • High-sensitivity electrode material for glucose non-enzymatic sensor and preparation method of electrode material

    CN106290517A

  • Copper-based nano-composite structure-based portable micro-glucose enzyme-free sensing electrode as well as preparation method and application thereof

    CN110530944A

  • Cerium dioxide modified copper hydroxide composite electrode and application thereof in glucose sensor

    CN111796014A

  • Nano-porous copper composite microelectrode, preparation method thereof and application of nano-porous copper composite microelectrode in enzyme-free glucose detection

    CN112578010A

  • Copper-tin composite material and preparation method and application thereof

    CN113136597A